Chemerin-activated functions of CMKLR1 are regulated by G protein-coupled receptor kinase 6 (GRK6) and β-arrestin 2 in inflammatory macrophages. (February 2019) - Serafin, D. Stephen; Allyn, Brittney; Sassano, Maria F.; Timoshchenko, Roman G.; Mattox, Daniel; Brozowski, Jaime M.; Siderovski, David P.; Truong, Young K.; Esserman, Denise; Tarrant, Teresa K.; Billard, Matthew J.
Highlights: A model for CMKLR1 receptor regulation on inflammatory macrophages is proposed. GRK6 helps recruit β-arrestin 2 to CMKLR1 after chemerin stimulation. CMKLR1 internalization in pro-inflammatory myeloid cells following chemerin stimulation is mediated by β-arrestin 2. β-arrestin 2 and GRK6 negatively regulate migration of pro-inflammatory macrophages toward chemerin. β-arrestin 2 and GRK6 have non-redundant function as negative regulators of CMKLR1 signaling. Abstract: Chemerin receptor (CMKLR1) is a G protein-coupled receptor (GPCR) implicated in macrophage-mediated inflammation and in several forms of human arthritis. Analogous to other GPCR, CMKLR1 is likely regulated by G protein-coupled receptor kinase (GRK) phosphorylation of intracellular domains in an activation-dependent manner, which leads to recruitment and termination of intracellular signaling via desensitization and internalization of the receptor. The ubiquitously expressed GRK family members include GRK2, GRK3, GRK5, and GRK6, but it is unknown which GRK regulates CMKLR1 cellular and signaling functions. Our data show that activation of CMKLR1 by chemerin in primary macrophages leads to signaling and functional outcomes that are regulated by GRK6 and β-arrestin 2. We show that arrestin recruitment to CMKLR1 following chemerin stimulation is enhanced with co-expression of GRK6. Further, internalization of endogenous CMKLR1, following the addition of chemerin, is decreased in inflammatory macrophages from GRK6- and β-arrestin 2-deficient mice. These GRK6- and β-arrestin 2-deficient macrophages display increased migration toward chemerin and altered AKT and Extracellular-signal Related Kinase (ERK) signaling. Our findings show that chemerin-activated CMKLR1 regulation in inflammatory macrophages is largely GRK6 and β-arrestin mediated, which may impact innate immunity and have therapeutic implications in rheumatic disease.